1990
DOI: 10.1002/ajh.2830350105
|View full text |Cite
|
Sign up to set email alerts
|

Rapid improvement of thrombotic thrombocytopenic purpura with vincristine and plasmapheresis

Abstract: Many patients with thrombotic thrombocytopenic purpura (TTP) fail to respond to daily plasmapheresis and the results of alternative treatments have been inconsistent. Vincristine was given weekly with continued plasmapheresis to eight patients who were refractory to plasmapheresis, antiplatelet agents, and/or corticosteroids. A rapid response to the vincristine occurred in all eight patients in 5 days with a marked rise in the platelet count and resolution of symptoms. The results in these patients suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Anecdotal reports of the effectiveness of VCR in TTP [4-61 have been treated with caution [2,3,7], but our findings corroborate those of Welborn et al [8], in demonstrating that many patients consistently respond 5 days after VCR therapy, an increase in the platelet count being the first evidence of thcrapeutic success. This temporal effect may give some insight into the pathophysiology of TTP, if it is postulated that VCR interferes with the abnormal platelet aggregation, thus leading to disease remission.…”
Section: Discussionsupporting
confidence: 93%
“…Anecdotal reports of the effectiveness of VCR in TTP [4-61 have been treated with caution [2,3,7], but our findings corroborate those of Welborn et al [8], in demonstrating that many patients consistently respond 5 days after VCR therapy, an increase in the platelet count being the first evidence of thcrapeutic success. This temporal effect may give some insight into the pathophysiology of TTP, if it is postulated that VCR interferes with the abnormal platelet aggregation, thus leading to disease remission.…”
Section: Discussionsupporting
confidence: 93%
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Successful vincristine use has been described in various small studies and case reports, usually as a rescue therapy in refractory TTP [17,[24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…From the collected reports of TTP patients treated with vincristine, compared with patients who did not receive vincristine, Welboru and coworkers concluded that vincristine was consistently effective in elevating the platelet count within 1 week [21,22]. Enhanced platelet production by the megakaryocytes is a likely explanation of vincristine's beneficial effect in TTP [12,21]. However, as vincristine disassembles the cellular microtubule matrix required for mitosis and cell division and hence, suppresses cellular and humoral immune responses, a direct immune modulation of the secretory endothelium cannot be excluded [6,7,9,16].…”
Section: Discussionmentioning
confidence: 97%
“…From the collected reports of TTP patients treated with vincristine, compared with patients who did not receive vincristine, Welboru and coworkers concluded that vincristine was consistently effective in elevating the platelet count within 1 week [21,22]. Enhanced platelet production by the megakaryocytes is a likely explanation of vincristine's beneficial effect in TTP [12,21].…”
Section: Discussionmentioning
confidence: 98%